1983
DOI: 10.1111/j.1476-5381.1983.tb10492.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two calcium antagonists, verapamil and fendiline, in an experimental model of myocardial ischaemia mimicking classical angina on effort

Abstract: 1 The effects of verapamil (0.15/kg) and fendiline (3 mg/kg) were studied in anaesthetized, thoracotomised dogs with a critical constriction of the left anterior descending coronary artery, paced in excess of the initial rate by 60-70 beats/min. Epicardial ST-segment elevation and changes in lactate uptake were used to assess the severity of myocardial ischaemia. 2 Both drugs prevented the ST-segment elevation and the reduced lactate uptake that resulted from atrial pacing. 3 The anti-ischaemic effect of fendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The doses of nicardipine HCI, verapamil (11.0-16.0 kg) were anaesthetised and ventilated artificially; a thoracotomy was performed through the left lateral fifth intercostal space of each animal. The technique used was adapted from that described by Szekeres et al (1976) and Csik et al (1983), using only an electrophysiological indicator at the onset of the post-ischaemic recovery phase to represent oxygen/metabolic debt. Instead of inducing partial obstruction to flow through the mid-region of the left anterior descendingartery (LAD), bymeansofconstricting a flexible cannula system linking autoperfused blood to a femoral or carotid artery, a partially snared ligature was applied.…”
Section: Preparation Of Test Drugsmentioning
confidence: 99%
“…The doses of nicardipine HCI, verapamil (11.0-16.0 kg) were anaesthetised and ventilated artificially; a thoracotomy was performed through the left lateral fifth intercostal space of each animal. The technique used was adapted from that described by Szekeres et al (1976) and Csik et al (1983), using only an electrophysiological indicator at the onset of the post-ischaemic recovery phase to represent oxygen/metabolic debt. Instead of inducing partial obstruction to flow through the mid-region of the left anterior descendingartery (LAD), bymeansofconstricting a flexible cannula system linking autoperfused blood to a femoral or carotid artery, a partially snared ligature was applied.…”
Section: Preparation Of Test Drugsmentioning
confidence: 99%
“…In this experiment, BP was controlled at a constant level to avoid disturbance of the coronary action of the com pound due to hypotension. This ischemic heart model mimics, in certain aspects at least, the alterations in myo cardial oxygen demand and supply in classical angina pectoris, and it has been reported to be useful for the evaluation of potential antianginal drugs (9,18). Using a similar model, Szekeres et al (9) found that a 10-min i.v.…”
Section: Discussionmentioning
confidence: 99%
“…In open-chest anesthetized dogs D600 significantly elevated myocardial blood flow in the non-ischemic area, but did not influence blood flow in the ischemic region [251] in contrast to the effect of verapamil, which either increased CF to the ischemic area [112] or caused a coronary steal from the ischemic area of the myocardium [128]. Ischemia and reperfusion-induced arrhythmias were reduced by D600 in rats [252], dogs [253] and guinea-pigs [254].…”
Section: D600 (Gallopamil) Animal Studies With D600mentioning
confidence: 96%
“…This effect is often not homogenous but a redistribution of the available CF can be seen. In some cases, CF of the ischemic area is increased improving the myocardial oxygen supply/oxygen requirement ratio [112] which is again beneficial. 7.…”
Section: Potential Mechanisms Behind the Antiarrhythmic Actions Of Ccasmentioning
confidence: 99%